PERAN GOOD CORPORATE GOVERNANCE (GCG) TERHADAP TINGKAT KONSERVATISME AKUNTANSI - Ign. Novie Endi Nugroho; Devina Putri Sihono (Media Akuntansi, 2018)
The objective of this research is to investigate the effect of board characteristics as part of corporate governance to conservatism in financial reporting. The board characteristics that was applied in this research are independency of boards, managerial ownership, existence of audit committee, board size and the number of boards meeting. This research uses two measurements of conservatism, accrual as accounting based measure and book to market ratio as market based measure, also uses control variable, that are institutional ownerships, size and leverage. The population in this research are all of the manufacture firm listed in the Indonesia Stock Exchange (IDX) for the period 2013-2015. Total sample in this research are 30 firm selected by purposive sampling. Data analyzed by classic assumption tests and examination hypothesis by multiple linear regression method. The result of this research show that boardsize, leverage, and size has significant effect to conservatism measured by accrual, while institutional ownerships and size has significant effect to conservatism measured by book to market ratio.